Abscisic Acid Mediates Grafting-Induced Cold Tolerance of Watermelon via Interaction With Melatonin and Methyl Jasmonate - Guo, Yanliang; Yan, Jingyi; Su, Zhuangzhuang; Chang, Jingjing; Yang, Jianqiang; Wei, Chunhua; Zhang, Yong; Ma, Jianxiang; Zhang, Xian; Li, Hao (Frontiers in Plant Science, 2021)
Grafting is widely used to increase plant defense responses to various stresses. Grafting-induced cold tolerance is associated with the increase of the antioxidant potential of plants; however, the underlying mechanisms remain unclear. Here, we found that pumpkin rootstocks promote antioxidant enzyme activities and alleviate cold-induced oxidative damage, accompanied by increased abscisic acid (ABA), melatonin, and methyl jasmonate (MeJA) levels in leaves. Increased ABA accumulation in leaves was attributed partly to the increased ABA levels in rootstocks. ABA induced antioxidant enzymes activities and the accumulation of melatonin and MeJA, while inhibition of ABA synthesis blocked the rootstock-induced antioxidant activity and the accumulation of melatonin and MeJA under cold stress. Melatonin and MeJA application also enhanced ABA accumulation in leaves after cold exposure, whereas inhibition of melatonin or MeJA synthesis attenuated the rootstock-induced increase of ABA. Moreover, melatonin and MeJA application alleviated cold-induced oxidative stress, but inhibition of melatonin or MeJA synthesis lowered the rootstock- or ABA-induced antioxidant potential and tolerance to cold. These findings indicate that ABA plays an important role in the grafting-induced cold tolerance by promoting the accumulation of melatonin and MeJA, which in turn, promote ABA accumulation, forming a positive feedback loop.